Analysis of the efficiency of enterprises in the field of energy and sustainable development: European experience - Qiming Sun; Vlasova Irina; Mustafina Olga; Rykov Andrey; Kolchina Vera; Moiseenko Svetlana (E3S Web of Conferences)
The energy sector plays a pivotal role in driving sustainable development across Europe. This paper analyzes the effectiveness of enterprises operating in the field of energy and sustainable development by examining European experiences. Through a bibliographic analysis of recent studies and a comparative assessment of different countries, the research identifies key factors contributing to enterprise success in this sector. The study employs a mixed-method approach, combining quantitative data analysis with qualitative case studies to provide a comprehensive understanding of the operational efficiencies and challenges faced by these enterprises. The findings highlight the importance of innovation, policy frameworks, and public engagement in enhancing enterprise effectiveness. Recommendations are provided for policymakers and industry stakeholders to foster a more sustainable and efficient energy sector.